Understanding Public Debates : What Literary Studies Can Do. - Gurr, Jens Martin (Oxford : Taylor & Francis Group, 2024)
Understanding Public Debates presents case studies including Milton's Paradise Lost and P.B. Shelley's 1820 Reform essay to explore how texts stage these debates by means of multiple perspectives, narrative situations, or ambiguities.
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- Credits List -- Introduction -- 1 The History of Ideas and the Long Shadow of Plato: Milton, Shelley and Problems of Liberty and Liberalism -- 2 Complicating the "Culture Wars": Rereading The Human Stain -- 3 America the Beautiful? Neil Young's Explorations of Genocide, Racism and the Foundations of "America" -- 4 Edward Young's Abysmal "Sea Odes": Mercantilism, Free Trade and Globalization -- 5 Cli-fi Novels as Models of and for Climate Futures -- 6 Understanding Conflicts through Conflict Narratives: Narrative Path Dependencies and the Chances for Compromise -- By Way of Conclusion: Ten Theses -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books